Juridical Analysis of the Application of the Principle of Contractual Balance in the Law of Agreements - Irfan Ardiansyah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
In the law of agreements, standard contracts have long been used in various contracts. The use of standard agreements is closely related to economic advancements that demand efficiency in cost, time, and energy expenditure. Standard agreements do not reflect the principle of balance between the parties in the agreement. The imbalance in positions in standard agreements is caused by the parties having unequal bargaining positions, resulting in "unreal bargaining." The purpose of this research is to understand the implementation of the principle of balance in agreements that use standard agreements. The method used in this research is normative, referring to legal norms found in regulations, using qualitative data and a descriptive-analytical approach. The research results indicate that imbalance occurs when the parties are in different economic strengths. The balance of an agreement is not solely determined by the positions of the parties but also by aspects of good faith. There are three aspects for the balance in an agreement to be achieved: the actions of the parties, the content of the agreement, and the implementation of the agreement. Ultimately, this will become binding for the parties involved.